EXPLORING STUDENTS’ INTEREST IN LEARNING ENGLISH AS A FOREIGN LANGUAGE THROUGH TRADITIONAL GAMES IN 2nd GRADERS - nurasid, Ami; Pasaribu, Arsen Nahum; Sinambela, Erika; Zour, Minliw; Wag, Yong (English Education Department at FKIP Nommensen University, 2025)
This study investigates students’ interest in learning English as a foreign language through traditional games in primary school. Using a qualitative descriptive method, the research focuses on student interest based on classroom observations and interviews, applying Schiefele’s (2009) indicators of student interest. The study population includes grades 2A, 2B, and 2C (87 students) at SDIT Permata Hati, Tebing Tinggi. A purposive sample of 29 students from grade 2B was selected. Data collection involved interviews and classroom observations. The findings indicate that a majority of students show high interest in learning English through traditional games. During game-based activities, 96% of students demonstrated positive emotional responses such as excitement and enthusiasm, reflecting key indicators of interest. These results suggest that traditional games can effectively enhance student motivation and engagement in English learning. The findings offer practical implications for English teachers in utilizing traditional games as instructional media. Moreover, the study recommends further research to explore the effectiveness of traditional games in secondary school contexts, particularly in enhancing interest and developing language skills such as listening, speaking, reading, and writing.